Are We Reaching the Limits of Homo sapiens? - Marck, Adrien; Antero, Juliana; Berthelot, Geoffroy; Saulière, Guillaume; Jancovici, Jean-Marc; Masson-Delmotte, Valérie; Boeuf, Gilles; Spedding, Michael; Le Bourg, Éric; Toussaint, Jean-François (Frontiers in Physiology, 2017)
Echoing scientific and industrial progress, the XXth century was an unprecedented period of improvement for human capabilities and performances, with a significant increase in lifespan, adult height, and maximal physiological performance. Analyses of historical data show a major slow down occurring in the most recent years. This triggered large and passionate debates in the academic scene within multiple disciplines, as such an observation could be interpreted as our upper biological limits. Such a new phase of human history may be related to structural and functional limits determined by long term evolutionary constraints, and the interaction between complex systems and their environment. In this interdisciplinary approach, we call into question the validity of subsequent forecasts and projections through innovative and related biomarkers such as sport, lifespan and height indicators. We set a theoretical framework based on biological and environmental relevance rather than using a typical single-variable forecasting approach. As demonstrated within the article, these new views will have major social, economical and political implications.